Fear of Death Among the Youth: Gender Perspective in Nepalese Context - Karki, Tej Bahadur; D’Mello, Laveena (International Journal of Atharva, 2024)
Background & Objective: Death is an inevitable truth though people perceive it differently. The study investigates the attitudes of Nepalese youth towards death, addressing a significant research gap in understanding how cultural, religious, and social factors shape their perceptions. Methods: A quantitative cross-sectional study was conducted with 196 college students using a random sampling technique. The Death Attitude Profile-Revised (DAP-R) was employed to measure attitudes toward death, utilizing a five-point Likert scale. The reliability and validity of the instrument were assessed through KMO and Bartlett's Test, factor loading values, and Cronbach’s Alpha. Key Findings: The results indicated a notable difference (p < 0.05) in death anxiety between genders, with females exhibiting higher levels of anxiety compared to males. The study found that a significant percentage of respondents expressed discomfort and anxiety regarding the concept of death, highlighting the need for targeted interventions. Conclusion & Recommendation: The findings underscore the necessity for educational programs that address death anxiety, particularly among young women. Future research should explore the underlying reasons for gender differences in death attitudes and consider cross-cultural comparisons to enhance the generalizability of the results. Implementing support programs could contribute to improved mental health and quality of life for the youth.